Workshop on Preparing Elementary School Teaching Materials using Technology Integration Planning (T.I.P.) Model in Cintalanggeng, Tegalwaru, Karawang Regency - Makbul, M.; Ferianto, Ferianto; Rochimah, Nur; Karnia, Nia; Munafiah, Nida'ul; Nuraini, Siti; Fauzia Apriyanti, Fiki Zahara; Nur Oktaviani, Malika; Ramdani , Teguh (Lembaga Dongan Dosen, 2024)
This research aims to provide an overview of the implementation of activities and results of the Workshop on Preparing Elementary School Teaching Materials using the Technology Integration Planning (T.I.P.) Model in Cintalanggeng Village, Tegalwaru District, Karawang Regency, the method used This section explains the methods used to complete the implementation of community service. It contains information related to service targets, activity locations, activity materials, and activity evaluations, including complete information for readers if they want to do the same thing. The origin and quantity of the materials used must be explained. How data works, and analysis must be written clearly and concisely. Modifications and working methods that have been published mention the source and explain the modified part. When using a statistical test, write the method, for example, RCBD. In this section, one type of method or a combination of several methods can be used. Increasing digital literacy skills in Cintalanggeng Village requires a systematic and inclusive approach. This workshop is designed to provide an in-depth understanding of the Technology Integration Planning (T.I.P.) model and provide practical training for educators. The Workshop on Preparing Elementary School Teaching Materials using Technology Integration Planning (T.I.P.) The model in Cintalanggeng Village significantly contributes to increasing teacher competency in using technology for teaching. By adopting a relevant theory-based approach, this workshop helps teachers develop more interesting and effective teaching materials and encourages continuous professional development and collaboration between teachers. The results of this workshop will positively impact the quality of education in the village, improve students' technology skills, and prepare them to face future challenges.